AB0425 Silent lupus nephritis in protocol biopsy after complete remission. (23rd January 2014) - Moya, P.; Díaz, M.; Arce, Y.; Castellví, I.; Diaz-Torné, C.; Geli, C.; Sarmiento, M.; Ballarin, J.; de Llobet, J. M.
Abstract : Background: Renal biopsy is an essential tool in lupus nephritis (LN) diagnose, It is also useful to establish prognosis. In general biological markers as complement, Anti ADN autoantibody are used to determine lupus clinical activity and to predict risk to have a renal flare. However, the literature reports a low sensitivity (50-70%) and specificity (<75%) to predict renal flares. In fact renal Biopsy remains as the gold standard for LN evaluation. Objectives: To study silent lupus nephritis (SLN) frequency in protocol renal biopsy made 2 years after clinical complete remission. Methods: A retrospective and descriptive study was performed. The population comprised patients diagnosed with LN that, after a course of treatment, accomplished clinical criteria for complete remission (defined as: urine protein/creatinine ratio <50 mg/mmol, <3 red blood cell in urine and, creatinine that return to baseline level). Demographic data, SLEDAI score, anti-DNA antibody and complement as well as histological type (using LN 2004 INS/RPS classification), activity and chronicity index, were recorded. Diagnostic criteria for SLN were: renal histology compatible with type II, III, IV, V and VI in renal biopsy and clinical criteria for complete remission. Results: Nine patients, 7 women and 2 men with a mean age of 24.2 years (at renal flare time) were included. SLEDAI mean was 12.6, 2 were on treatment with Mycofenolate (MYC), 1 was on hydroxychloroquine (HCQ), 1 on Azatioprine (AZA), 1 on Lefluonomide and 4 were not on any treatment. First biopsy results were: 5 patients had Type IV, 2 patients had type II, 1 patient had type III+V and 1 patient had II+V. Activity index was 4 and chronicity index was 1.77. All patients reached complete remission after treatment (cyclophosphamide (CYC) 7, AZA 1 and the last with Rituximab, all of then receive prednisone and maintenance therapy with MYC). Protocol biopsy was performed at a mean time of 24 month after treatment, 6 patients improved histology, in 2 patients no changes were found and 1 patient worsen (table 1 ). Activity index improved from 4 to 0.44 and chronicity from 1.77 to 1.55. All patients met NSL clinical criteria at the time of protocol biopsy. Conclusions: NLS is an underdiagnosed entity in patients with SLE. Renal biopsy remains as the gold standard for diagnosis. Although larger studies are required, our study supports that protocol biopsies, once clinical remission is reached, are needed to determine histological remission. References: Díaz MM, Ballarín J. Nefropatía lúpica silente. Semin Fund Esp Reumatol. 2012. doi:10.1016/j.semreu.2011.10.002. Zabaleta-Lanz M, Vargas-Arenas RE, Tápanes F, Daboin I, Pinto JA, Bianco NE. Silent Nephritis in systemic lupus erythematosus. Lupus. 2003, 12:26-30. Weening J, D'Agati V, Schwartz M, Seshan S, Alpers C, Appel G, et al., on behalf of the ISN, RPS Working. The classification of glomerulonephritis in systemic lupus erythematosus revisited. J Am Soc Nephrol. 2004;15:241–50. Disclosure of Interest: None Declared